Application of tubular ceramic membranes for reuse of wastewater from buildings - Ahn, KH; Song, JH; Cha, HY (PERGAMON-ELSEVIER SCIENCE LTD, 1998)
This research investigated the possibility of applying ceramic membranes for simple and compact treatment to reuse wastewater generated from hotel buildings for secondary purposes such as toilet flushing water. The tested membranes were ultrafiltration (UF) and microfiltration (MIF) membranes of 15 kDa, 300 kDa, and 0.1 mm. Parameters such as transmembrane pressure, crossflow velocity, MWCO/pore size were changed and the performance of the membranes and the quality of the permeate observed. Since the average particle size of the influent wastewater was 2.18 pm, larger than the pore size of the membranes tested, the effect of MWCO/pore size on the filtration performance plas marginal. When a pseudo-steady state was reached, permeate flux increased with increased crossflow velocity. Furthermore, it was better to adopt turbulent flow (Re>20,000) rather than laminar flow in order to maintain constant transmembrane pressure and system stability. The optimum transmembrane pressure was found to be 150 kPa; a higher pressure will density the cake layer unnecessarily on the membrane surface which will induce quicker membrane fouling. When energy consumption was compared, MF with: 0.1 Gun, which was capable of producing higher permeate flux in the initial phase of experimentation than other tested membranes, was found to be the least energy consuming; the effect of other parameters besides the pore size of the membrane was negligible on the energy efficiency. The quality of permeates obtained from all the experiments investigated in this research satisfied the guidelines set by the Korea Ministry of Environment for the reuse of wastewater for secondary applications such as in toilet flushing water. (C) 1998 Published by Elsevier Science Ltd. All rights reserved.
Keywords: CROSS-FLOW MICROFILTRATION; SUSPENSIONS